(untitled) (Journal of Organizational Psychology, 2017)
Organizations are increasingly shifting from defined benefit (DB) to defined contribution (DC) retirement plans. While such changes may lower organizational costs, the shift to DC plans has been conducted without consideration of how these changes may affect the exchange relationship that exists between organizations and employees. Drawing on previous benefits research and organizational support theory, I develop propositions regarding how retirement pension plans may affect a range of employee outcomes and provide a warning to researchers and practitioners not to overlook possible important side effects of the shift from DC to DB plans.